2011
DOI: 10.1007/s11250-011-9836-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various plant protein sources in high-quality feed block on feed intake, rumen fermentation, and microbial population in swamp buffalo

Abstract: This study was designed to determine effect of various plant protein sources in high-quality feed block (HQFB) on feed intake, rumen fermentation, and microbial population in swamp buffalo. Four rumen-fistulated swamp buffaloes (Bubalus bubalis) were randomly assigned according to a 4 × 4 Latin square design. Four kinds of plant protein sources (coarse rice bran (CRB), cassava hay (CH), Phaseolus calcaratus hay, and mulberry hay (MH)) were mixed in the HQFB. HQFBs were allowed to be licked at free choice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…Feed block intake was similar among cattle in the present study and was at 0.3 kg/d and this indicated that U-cas can replace urea in feed block for Thai native beef cattle without adverse intake. The feed block intakes in the present investigation were similar to Foiklang et al (2011) who reported that the range of feed block intake of swamp buffalo were from 0.27 to 0.31 kg/d. Though the intake of feed block-was not changed by supplementation of U-cas; however, the feed block-supplementation enhanced the intake of basal roughage significantly (P<0.05).…”
Section: Intake Of Rice Straw Concentrate and Feed Blockssupporting
confidence: 90%
See 3 more Smart Citations
“…Feed block intake was similar among cattle in the present study and was at 0.3 kg/d and this indicated that U-cas can replace urea in feed block for Thai native beef cattle without adverse intake. The feed block intakes in the present investigation were similar to Foiklang et al (2011) who reported that the range of feed block intake of swamp buffalo were from 0.27 to 0.31 kg/d. Though the intake of feed block-was not changed by supplementation of U-cas; however, the feed block-supplementation enhanced the intake of basal roughage significantly (P<0.05).…”
Section: Intake Of Rice Straw Concentrate and Feed Blockssupporting
confidence: 90%
“…Increasing in DMI of rice straw by U-cas supplementation in the feed block licks was due to the availability of limiting nutrients (sulfur from CaSO 4 ) and progressive change in rumen fermentation. Similarly, Wanapat and Khampa (2006) and Foiklang et al (2011) found that supplementation of feed blocks could increase feed intake of urea-lime treated rice straw and total intakes while no change on feed blocks intakes were found among treatments. Moreover, steers consuming formulated molasses block; containing base ingredients of beet molasses, cane molasses, or concentrated separator by-product (Greenwood et al, 2000) and varying levels of urea and/or feed grade biuret as CP sources (Löest et al, 2001) increased feed intake of low-quality prairie hay.…”
Section: Intake Of Rice Straw Concentrate and Feed Blocksmentioning
confidence: 93%
See 2 more Smart Citations
“…Nilai pH yang diperoleh dalam penelitian ini berada pada kondisi optimal untuk menjamin pertumbuhan dan aktifitas mikroba rumen (pH 6,30 -7,00) (Orskov, 1982). Hasil penelitian ini tidak jauh berbeda dengan hasil penelitian Foiklang et al (2011) Paling tingginya total VFA pada perlakuan B sejalan dengan peningkatan kecernaan zat makanan, namun semakin tinggi level pakan suplemen yang diberikan pada perlakuan C dan D semakin rendah total VFA yang dihasilkan, hal ini sejalan dengan kecernaan yang semakin rendah, karena VFA merupakan hasil akhir fermentasi karbohidrat oleh mikroba rumen. Peningkatan kadar VFA menunjukkan peningkatan kandungan protein dan karbohidrat pakan yang mudah larut.…”
Section: Peubah Yang Diamatiunclassified